2016
DOI: 10.1186/s12888-016-0936-0
|View full text |Cite
|
Sign up to set email alerts
|

The latent structure of post-traumatic stress disorder among Arabic-speaking refugees receiving psychiatric treatment in Denmark

Abstract: BackgroundRefugees are known to have high rates of post-traumatic stress disorder (PTSD). Although recent years have seen an increase in the number of refugees from Arabic speaking countries in the Middle East, no study so far has validated the construct of PTSD in an Arabic speaking sample of refugees.MethodsResponses to the Harvard Trauma Questionnaire (HTQ) were obtained from 409 Arabic-speaking refugees diagnosed with PTSD and undergoing treatment in Denmark. Confirmatory factor analysis was used to test a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
1
13
1
1
Order By: Relevance
“…In line with most of the previous item level and factor analytic studies of PTSD (Wang et al, 2011, 2015b; Liu et al, 2014a,b; Vindbjerg et al, 2016), we observed that the psychogenic amnesia symptom (item 8) contributed poorly to all of the factors and to the overall structure of PTSD. In our study, the prevalence and standardized factor loading for psychogenic amnesia item was lower than all other PTSD symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…In line with most of the previous item level and factor analytic studies of PTSD (Wang et al, 2011, 2015b; Liu et al, 2014a,b; Vindbjerg et al, 2016), we observed that the psychogenic amnesia symptom (item 8) contributed poorly to all of the factors and to the overall structure of PTSD. In our study, the prevalence and standardized factor loading for psychogenic amnesia item was lower than all other PTSD symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, in contrast to our results, most studies provided evidence for the recently proposed DSM-5 PTSD model (e.g. Fodor et al, 2015; Vindbjerg, Carlsson, Mortensen, Elklit, & Makransky, 2016). …”
Section: Discussioncontrasting
confidence: 99%
“…[52]. Vindbjerg et al [53] assessed the factorial structure of PTSD in an Arabic speaking population of refugees with the Harvard Trauma Questionnaire [54]. The results of their study indicate that the construct of PTSD is valid among this population.…”
Section: Discussionmentioning
confidence: 99%